The Influence of Kebar Grass Infuse to Mice (Mus musculus) Spermatogenesis - Paula Nency Lefaan (Jurnal Sain Veteriner, 2014)
This study was aim to examine the effect of grass infusion kebar (Biophytum petersianum) to increase the activity of spermatogenesis in male mice. This research was conducted at the Laboratory of Botany University Discourse Kristen Duta Yogyakarta, Laboratory of Experimental Animal Care Unit and Unit III LPPT Gadjah Mada University in April 2009 to May 2009 using Swiss strain male mice aged 2.5 months as many as 25 tails, which are grouped in 5 groups treated with different concentrations, 0% (control), 1%, 3%, 5%, and 10% for 30 days, 2 times a day at a dose of 0.5 ml each time. Results of TLC method proves that these plants contain three types of chemical compounds that could potentially impact the process of spermatogenesis, ie, saponins, flavonoids and tannins. The analysis showed an increase in activity with increasing concentrations of spermatogenesis up to a concentration of 5% (spermatogonia: 226, primary spermatocytes: 227, secondary spermatocytes: 377, spermatids: 302) with a significant value of 0.432. Yet, at a concentration of 10% actually decreased spermatogenesis activity due to negative feedback. Conclusion: Infuse kebar grass proved to increase the activity of spermatogenesis, but at concentrations that are too high can cause a decrease in spermatogenesis activity.